Temporal and spatial variations and impact factors of nutrients in Bohai Bay, China. (March 2019) - Liu, Xihan; Liu, Dongyan; Wang, Yujue; Shi, Yajun; Wang, Yanxia; Sun, Xiyan
Abstract: The temporal and spatial distributions of dissolved inorganic nitrogen (DIN), dissolved inorganic phosphorus (DIP), and dissolved silicate (DSi), and their long-term changes were investigated in Bohai Bay (BHB) in spring, summer, and autumn (2013–2014). The high DIN values were consistently distributed in the western inshore waters, mainly determined by terrestrial factors, e.g., riverine input, while DIP and DSi were mostly distributed in the southern coastal waters, the central BHB, or near the sea port Caofeidian in northern BHB, largely related to non-terrestrial factors, e.g., sediment release. Based on the nutrient distribution, BHB could be partitioned into western and eastern parts, with −15 m depth as the separation. The long-term variations of nutrients since 2000 showed an increase in DIN and decreases in DIP and DSi. Relatively slow changes in DIN and DIP and a rapid decrease in DSi were exhibited in summer, which was associated with precipitation and sediment release. Highlights: BHB is partitioned into two parts based on nutrient sources and impact factors. In western BHB, terrestrial inputs lead to the consistent high values of DIN. In eastern BHB, non-terrestrial factors impact DIP and DSi distributions. Since 2000, DIN increased together with DIP and DSi decreased. Summer showed slow changes in DIN and DIP, and a rapid change in DSi.